Analysis of the Effects of Defense Expenditures on Income Distribution and Economic Development with Panel Asymmetric Causality Test: Brics Countries and Turkey Case - Gül, Ekrem; Torusdag, Mustafa (International Journal of Contemporary Economics and Administrative Sciences, 2019)
In this study, for BRICS countries and Turkey defense spending economic development and income distribution relationship is examined for the period 1995-2015. High defense expenditures are on the agenda as an important research topic in the world and in our country. Therefore, the effects of defense expenditures on income distribution and economic development of countries can be determined by examining these three variables. For the BRICS countries and Turkey, to examining the impact of defense spending and income distribution to economic development too much work not found. Westerlund (2008) found that the cointegration relationship between the main variables and the negative components was not detected in the long term, whereas long-term relationship was found between the positive components. According to the results of the asymmetric panel causality analysis, only one-way causality from economic growth to defense expenditures was determined between economic growth and defense expenditures in the period 1995-2010, while there was no causality from defense expenditures to economic growth. One-way causality from income inequality to defense expenditures was identified between 1995 and 2010 in terms of income inequality and defense expenditures, while bi-directional causality was detected in 1996-2011 period. In the period of 2000-2015, it is concluded that there is a one-way causality from defense expenditures to income inequality.